Strengthening Tolerance Values in Civics Learning in MI/SD - Rizka Ardini; Mutia Fathia Rahmah (IKAMAS: Jurnal Informasi Keagamaan, Manajemen dan Strategi, 2023)
This study aims to determine the relationship between knowledge and attitudes of tolerance in the subject of Civics education of students at SD Negeri 009 Dumai, Riau. The subjects in this study were 31 students of class IVA, this type of research uses quantitative descriptive with correlation methods. Data collection techniques using interview techniques via WhatsApp/online. In the Framework of Strengthening the Value of Tolerance in Civics Learning in MI/ Religious Elementary Schools Between Students Through Civics Learning. The implementation of character education in Civics learning is a manifestation of the attitudes shown by students during the process of learning Civics at school, at home, and in the community. The author aims to explain the Role of Teachers in implementing reinforcement, instilling the value of tolerance character to students using descriptive methods through reading books and journals which get results that there is an implementation of increasing the value of tolerance character through Civics learning in Elementary Schools for teachers and learning outcomes.